Pelatihan Manajemen Keuangan Bagi Siswa di SMK Karmel Kota Tangerang - Nana Sutisna; Yanti Puspa Rini; Toni Yoyo; David Kiki Baringin; Henry Gunawan; Juan Barus Gultom; Suhendra Suhendra; Triscna Juwita; Stephanie Prily Winata (Lembaga Pengembangan Kinerja Dosen, 2024)
Management is a series of activities that include planning, organizing, directing and controlling organizational resources in order to achieve goals efficiently and effectively (Stoner, 2009). In this context, financial management training at Karmel Vocational School is a strategic step to prepare students to face the challenges of the digital era business world. Qualitative research through observations, interviews and documentation studies shows that this training has had a significant positive impact. Students gain an understanding of financial management, online marketing strategies, product innovation, and the use of digital platforms to build brand awareness and measure the effectiveness of marketing campaigns. Apart from that, this training succeeded in developing proactive, creative, innovative and adaptive attitudes which are important in the modern business world. The results of the training showed an increase in students' self-confidence to start an independent business, reduce dependence on formal work, and consider financial management as a career path . To increase effectiveness, it is recommended to expand the scope of training to include e-commerce and data analysis, strengthen partnerships with industry players, and integrate training into the vocational school curriculum. Thus, it is hoped that this training will be able to increase the competitiveness of Karmel Vocational School students, prepare them to face the dynamic business world, and support the sustainability of skills-based learning programs.